Synthesis of Molecularly Imprinted Polymers with Magnetite Cores for Ibuprofen Adsorption - Halimah Fahri; Muhammad Ali Zulfikar; Muhammad Yudhistira Azis (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Ibuprofen (IBP) is a pollutant that is widely found in aquatic environments due to pharmaceutical waste and the metabolic results of humans who consume the drug. These compounds can cause damage to aquatic ecosystems, genotoxicity, and aquatic toxicity and are harmful to human health. This study aims to selectively adsorb IBP using magnetic molecularly imprinted polymers (MMIPs) synthesized from ibuprofen (IBP) as a template molecule, methacrylic acid (MAA) as a functional monomer, and divinylbenzene (DVB) as a crosslinker with a mole ratio of 1:4:20 in acetonitrile porogen solvent using a bulk polymerization method. Fe3O4 nanoparticles and MMIPs were characterized using X-ray diffraction (XRD), Fourier Transform Infra-Red (FTIR), and Scanning Electron Microscope (SEM). IBP adsorption reached optimum conditions at pH 3 with a contact time of 90 minutes and a mass of 25 mg of adsorbent. The adsorption performance of MMIPs for IBP was evaluated by adsorption isotherms and adsorption kinetics. Adsorption of IBP by MMIPs followed the Langmuir adsorption isotherm model with an adsorption capacity of 227.24 mg/g. Kinetic studies showed that the adsorption process followed a pseudo-second-order adsorption kinetic model. MMIPs can adsorb IBP selectively even in the presence of interfering compounds, are easily separated from the solution, and can be used repeatedly with good adsorption ability. Hence, it is efficient and promising for removing IBP from aqueous media.